THE ROLE OF DEMOGRAPHIC FACTORS ON INVESTMENT INTENTIONS DURING COVID-19 - Nyimas Dewi Murnila Saputri; Agung Putra Raneo; Fida Muthia (Jurnal Ekonomi, 2023)
This study aims to influence demographic factors on investment intentions during COVID-19. Demographic factors used in this study as measurement variables are gender, education, and occupation. This research will be helpful and meaningful for individuals who are interested in investment activities. The sampling technique uses a non-probability sampling method. The sample in this study had an age range of 22-41 years. The total sample used in this research was 200 respondents according to the required criteria. This research was conducted throughout Indonesia using a survey method through online questionnaires. The data analysis used in this research is regression analysis. The results of this study show that the demographic factors used in this study have not been able to measure investment intentions during the COVID-19 pandemic.